Best Answer

6*3-6*2-12x

v v

18 - 12-12x

v v

6-24x

-6 -6

something like that..

Q: How do you solve 6x3-6x2-12x equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

x: x2 - 81 = 0

y=±√15

16

4n2-25 = 0 4n2=25 n2=6.25 n=sqrt(6.25) n= +2.5 or -2.5

In order to solve this equation you need to know what -28x-2 equals. If you were to assume it was 0 then x = 0.071 rounded

Related questions

2sinx+1 equals 0

For y - 2y - 3y equals 0, y equals 0.

many solutions

"x equals 0" is an equality, not an inequality. The question is, therefore, not consistent.

Suppose x3-4x = 0. To solve, factor: x3-4x = x(x2-4) = x(x+2)(x-2) = 0 Now, a product equals 0 if and only one or more of the factors equals 0, so set each factor to 0 and solve. The roots are 0,-2 and +2.

x: x2 - 81 = 0

Solve this problem -x squared -40x- 80 =0

x=2

10x=x 9x=0 x=0

Divide both sides by 8: m = 0

-y + y equals 0.

x=-.25.